2020
DOI: 10.1016/j.ijengsci.2020.103341
|View full text |Cite
|
Sign up to set email alerts
|

Fluid structure interaction study of stenosed carotid artery considering the effects of blood pressure

Abstract: Atherosclerosis is the most common Cardiovascular Disease (CVD) causing increased morbidity. Although atherosclerosis is a general disease involving several factors, it preferentially affects the wall of the vessel bifurcations. The employment of advanced Computational Fluid Dynamics (CFD) has the potential in shedding more light in the further understanding of the causes of the diseases and perhaps aid in the early diagnosis. In this study, a three-dimensional Fluid Structure Interaction (FSI) study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
(50 reference statements)
0
37
0
Order By: Relevance
“…In medium and smaller arteries, non-Newtonian assumption is valid as shear rate is lower than 100 s À1 and shear stresses depend non-linearly on the deformation rate [24]. A time varying velocity pulse is applied at inlet of both the carotid cases based on available literature [8]. A typical inlet velocity profile as shown in the Figure 4 is applied for both cases (a) and (b) without altered gravity behavior which contributes to sleeping posture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In medium and smaller arteries, non-Newtonian assumption is valid as shear rate is lower than 100 s À1 and shear stresses depend non-linearly on the deformation rate [24]. A time varying velocity pulse is applied at inlet of both the carotid cases based on available literature [8]. A typical inlet velocity profile as shown in the Figure 4 is applied for both cases (a) and (b) without altered gravity behavior which contributes to sleeping posture.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that hemodynamics of the carotid artery was very much affected by the geometry and flow conditions. Furthermore, regions of relatively low wall shear stress were observed post stenosis, which is a known cause of plaque development and progression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Grid independence test carried out for all aneurysm models adopted in the CFD study to optimise the element size for every aneurysm model and it is shown in Figure 3. A laminar flow model was used to simulate the steady flow in the carotid arteries with an RMS value of 10 -4 [27]. A maximum of 600 iterations was taken for convergence in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation of the upper arm low-ductility massage belt B and the forearm low-ductility massage belt B is carried out to improve the parameter design and optimization of the total rehabilitation module of the device. As an excellent finite element analysis software, ANSYS has been more and more used in biological simulation experiments ( Nowak et al, 2019 ; Aubert et al, 2020 ; Kumar et al, 2020 ). According to the biological structure of human upper limb, a 3D reconstruction of an upper limb model was carried out, and the simulation results were output by ANSYS software.…”
Section: Principle Of Device Designmentioning
confidence: 99%